Regular and chaotic quantum motions - Iacomelli, Guglielmo; Pettini, Marco (Physics letters. A, 1996)
In the framework of Bohm's interpretation of quantum mechanics, particles are subject to both classical and quantum forces and actually follow physical trajectories. A natural definition of chaos in quantum mechanics is therefore possible and it is measured by a quantum Lyapunov exponent. In order to test the effectiveness of this new definition of quantum chaoticity, we have comparatively studied a classical model and a truncated N-level quantum model of a hydrogen atom acted upon by an external electromagnetic field. We find direct evidence for the existence of quantum chaotic motions, for a chaotic transition and for a quantum attenuation of classical chaos in a broad range of external field amplitudes.